Changing the outcomes of newborns with surgical conditions at a tertiary-level hospital in Kenya: a cluster randomized trial - Peter Saula; Gideon Kikuvi; Yeri Kombe; Irene Marete (SpringerOpen, 2022)
Abstract Background Globally, 10% of neonatal mortality in low-/middle-income countries (L/MIC) is directly attributed to surgical conditions, and appropriate referral and transport of newborns to tertiary-level hospitals for surgical care often underlie their survival. This study aimed at evaluating the outcomes of newborns with surgical conditions in a low-resource setting, in the context of a structured standard operating procedure (SOP) for newborn transport.  Methods A cluster randomized controlled trial was conducted. Ten county hospitals that refer newborns with surgical conditions to the Moi Teaching and Referral Hospital (MTRH) were selected and randomized into intervention group (A) and control group (B). A structured standard operating procedure (SOP) for transport of newborns was introduced in the hospitals in group A via an education module. Thereafter, 126 newborns (63 in group A and 63 in group B) were enrolled, upon their admission to the MTRH. All the newborns from both groups of referring hospitals were given standard surgical care upon admission. Data on study variables was collected and analyzed, and the outcomes of the newborns in the two groups were compared to assess the effect of the structured SOP. Results The median age at admission was 4.1 days in group A and 4.6 days in group B. The top 4 surgical conditions were gastroschisis, hydrocephalus, Hirschsprung's disease, and anorectal malformations. There was a statistically significant difference (p < .05) in all parameters that measured the clinical status of the newborns at admission, in the two groups. Mortality rate was 3.2% in group A and 28.6% in group B (p < .001), and hospital stay was 11 days in group A and 18 days in group B. Conclusion Appropriate transport of newborns with surgical conditions significantly improved their outcomes at the MTRH. Level of evidence II